Cerita Rakyat Pesisiran Jawa Timur Perspektif Antropologis - Kusnadi Kusnadi (ATAVISME, 2008)
This paper is aimed to describe a research opportunity and the advantage of East Java coastal area folklore. A coastal area folklore implies values about conservation of surround resources relevant with the efforts to solve crucial problem in coastal area. Cultural values in coastal area need to be explore through a research.